Tudang Sipulung in Muslim Community of Peniti Luar (Identity, Islamic Value and Character Building) - Bayu, Bayu Suratman; Kurniawan, Syamsul (Khatulistiwa, 2019)
This research was conducted in the Peniti Luar village, Siantan Sub-district, Mempawah Regency, West Kalimantan Province, where the tradition ot tudang sipulung workshop is still being carried out. The focus of this research is to discuss some basic questions: First, why muslim communities in Peniti Luar are still retaining scavengers. Second, how do muslim communities in the village of Peniti Luar carry out the tudang sipulung. What Islamic values are relevant in tudang sipulung. And the fourth is what is its relevance in building character. This paper departs from a study in which the data obtained from interviews and observations on the location of the research which it conducted in depth. Keywords: Tudang Sipulung, Identity, Islamic Values, Character Building This research was conducted in the Peniti Luar village, Siantan Sub-district, Mempawah Regency, West Kalimantan Province, where the tradition ot tudang sipulung workshop is still being carried out. The focus of this research is to discuss some basic questions: First, why muslim communities in Peniti Luar are still retaining scavengers. Second, how do muslim communities in the village of Peniti Luar carry out the tudang sipulung. What Islamic values are relevant in tudang sipulung. And the fourth is what is its relevance in building character. This paper departs from a study in which the data obtained from interviews and observations on the location of the research which it conducted in depth. Keywords: Tudang Sipulung, Identity, Islamic Values, Character Building Kata Kunci:Tudang Sipulung, Identitas, Nilai Islam, Character Building